Investigating the landing kinetics factors and preparatory knee muscle activation in female handball players with and without dynamic knee valgus while performing single leg landing - Mansouri Reyhaneh; Bahrami Fariba; Rajabi Reza; Minoonejad Hooman; Kaczmarczyk Katarzyna (Sciendo, 2021)
Study aim: to examine the differences in landing kinetics factors (LKF) to assess the whole body stability and preparatory muscle activation (PMA) in female handball players with and without dynamic knee valgus.